Modelo de Planeación de Operaciones para la empresa Primadera SAS (2019)
One of the most important processes within companies is the planning of operations, since a large part of the activities carried out depend on this process, such as ensuring optimal inventory levels, guaranteeing service levels, reducing of costs, improvement of operational efficiency, customer satisfaction, among others. Due to the aforementioned, it is sought to develop an operations planning model for the company Primadera SAS, using Mixed Whole Linear Programming in order to contribute to better decision-making in the planning of its operations, since currently This company performs the process manually and empirically.